RANKL EXPRESSION AND METABOLIC CHANGES IN OVARIECTOMIZED RATS AND THE POSSIBLE PROTECTION BY VEGETABLE FORMULA. - El- Shobaky, Fawzy; Kassem, Seham S.; Hanafi, Emtenan,m.; Al Shafei, Moetazaa M.; Saleh, Zeinab A.; Badawy, Ibrahim; Abd El Kader, Madeha, M. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was to evaluate complications of osteoporosis in ovariectomized rats and the possibility to ameliorate these changes by consumption of vegetable formula. Furthermore, transcription of mRNA of RANKL gene was matched with bone mass density (BMD) and bone formation marker (human procollagen 1 N terminal peptide [PINP]). Methods: Thirty rats were divided into three groups. The first is non ovariectomized control group (NOVXC), the second is ovariectomized control group (OVXC), and the third is ovariectomized rats supplemented with the vegetable formula (OVXT). Animals were fed for 8 successive weeks. Animals were treated and sacrificed under the recommended ethics of laboratory animal's treatment. The vegetable mixture was formulated with the purpose to correct the bone compromise and supply all the presumed deficient elements and hormone. Results: Chemical analysis showed that the formulated vegetable mixture had a high amount of flavonoids as catechin (100 mg/100 g of dry weight) and polyphenols as tannic acid (1000 mg/100 g dry weight. Furthermore, it had high reducing power (1,1-diphenyl-2-picrylhydrazyl radical showed inhibition percentage of 91.81%.). Several phytochemicals necessary for bone health were demonstrated in the vegetable mixture using high-performance liquid chromatography. RANKL/GAPDH mRNA transcription ratio showed marked an increase in OVXC versus the control NOVXC rats (1.00 vs. 0.199, respectively) accompanied with a drop in BMD (0.157 vs. 0.25 mg/cm2, respectively) and PINP values (27.9±2.8 compared to NOVXC 34±2.4 μ/L, respectively). The vegetable mixture supplementation showed better values of BMD and PINP in OVXT group directed back toward normal (0.183 mg/cm2 and 29.35±3.4 μ/L, respectively). Furthermore, analysis of blood plasma of supplemented group showed lower blood glucose, lipid profile, and oxidative markers if compared to that in OVXC group. Conclusion: It may be concluded that the plant formula was effective to minimize health hazards in ovariectomized rats and maybe for postmenopause women. Perhaps longer time may be needed for more significant and clear effect.